Wavelet and Wavelet Packet Analysis For Image Denoising - Aymen Dawood Salman (Engineering and Technology Journal, 2009)
The denoising method based on wavelet or wavelet packet is used widely for image denoising. It is one of the most popular methods that depends on thresholding the wavelet coefficients using the Soft threshold. There are many methods used to get the threshold that is used in denoising image. In this paper, the amplitude of threshold is calculated depending on RMS error in order to get the best threshold related with the image information. The denoising results show that the wavelet packet is better than the wavelet method in analyzing the image coefficients of information